USING CIRCULAR INTUITIONISTIC FUZZY TOPSIS TO ELIMINATE THE HESITANCY IN THE FIELD OF AGRICULTURAL BIOLOGY - Gökkuş, Zeynep; Şentürk, Sevil; Alatürk, Fırat; Ali, Baboo (Anadolu Universitesi Bilim ve Teknoloji Dergisi-A: Uygulamali Bilimler ve Muhendislik, 2025)
Circular intuitionistic fuzzy sets (CIFSs) were introduced by Atanassov (2020) as a new extension of intuitionistic fuzzy sets. C-IFSs are represented by a circle of each element that is characterized by degrees of membership and non-membership. In a decision-making process based on experimental data, although uncertainty is low, hesitation can be high. In such cases, the decision-making process is affected by the decision-makers as well as the criteria. Therefore, there is a need to evaluate the expertise of decision-makers within the decision-making process. In Circular Intuitionistic Fuzzy Sets, where hesitation is represented, an approach is proposed for calculating decision-maker weights with the Technique for Order of Preferences by Similarity to Ideal Solution (TOPSIS), which is a multi-criteria decision-making method to eliminate hesitation. In this study, circular intuitionistic fuzzy sets were implemented into the TOPSIS method. The problem was handled from two different perspectives while creating the decision matrix. Sensitivity analyses were performed for both applications. These sensitivity analyses were carried out to examine the change in the ranking of the alternatives when the optimistic or pessimistic approaches of the decision makers, criterion weights, and the decision maker importance weights changed, respectively. In addition, intuitionistic and Pythagorean fuzzy TOPSIS methods were applied and presented as comparative analyses. According to the results obtained, the proposed approaches were satisfactory in eliminating the hesitation.